185k views
0 votes
-x-3y=14
x=4y


solve using substitution

2 Answers

4 votes
using
f1(x)= -x=3t =14

with f2(x) as x=4y

f1(f2)= -x-3y=14
F1(4y)= -(4y)-3y=14
= -4y-3y=14
= - 7y=14
= y= -2

Using the value of y, solve fo rx by entering the value in the original form of f1 or f2

-x-3y=14
-x-3(-2)=14
-x+6=14
x=-8

OR
x=4y
=4(-2)
= -8

Thus the solution is (x,y) = (-8,-2)
User Wis
by
5.2k points
3 votes
Solve both equations for one variable. Since the second equation is already solved for
x, we'll solve the other one for
x.


x=-14-3y and
x=4y are our two equations.

Now we can assume that if
x = -14-3y and
x=4y, we can assume that
-14-3y = 4y. If we solve for
y, we get that
y=-2. Plug in
y=-2 into either one of the equations, I'll use
x=4y.
x=4(-2) so [/tex]x=-8[/tex]. Know we know what
x and
y are, so we can put it in an orderned pair: (-8,-2)
User Tub
by
6.1k points